2009
DOI: 10.1007/s10620-009-1069-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vitamin D Deficiency in Chronic Liver Disease

Abstract: Vitamin D deficiency is universal (92%) among patients with chronic liver disease, and at least one-third of them suffer from severe vitamin D deficiency. African American females are at highest risk of vitamin D deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
231
7
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(257 citation statements)
references
References 22 publications
13
231
7
6
Order By: Relevance
“…In contrast with our results, Arteh et al [24] who reported that African American females with chronic liver disease are at higher risk of vitamin D deficiency.…”
contrasting
confidence: 99%
“…In contrast with our results, Arteh et al [24] who reported that African American females with chronic liver disease are at higher risk of vitamin D deficiency.…”
contrasting
confidence: 99%
“…It is well established that compromised liver function will affect an individual's ability to synthesize VD (Arteh, Narra, & Nair, 2010;Autier & Gandini, 2007;Krol et al, 2014), thus causing vitamin D deficiency in patients with liver disease. The targeted population in this Doctor of Nursing Practice (DNP) project are transplanted patients with sub-optimal serum 25(OH)D levels.…”
Section: Local Issue Of Vitamin D Deficiencymentioning
confidence: 99%
“…Chronic cholestasis (such as in primary biliary cirrhosis) [7], low levels of insulin-like growth factor-1 [8,9], impairment of J Gastrointestin Liver Dis, September 2016 Vol. 25 No 3: 323-329 receptor activator of nuclear factor κappa B ligand (RANKL) and osteoprotegerin system [10], vitamin D deficiency [11,12], low body mass index (BMI) [13], chronic alcoholism [14] and sedentary lifestyle [15] were implicated in HO pathogenesis. In CHC, the main mechanism seems to be an inflammatory response that increases release of cytokines with bone resorption due to osteoclast activation [16,17].…”
Section: Introductionmentioning
confidence: 99%